The problems of innovation in enterprises - D.O. Krikunenko (Marketing i Menedžment Innovacij, 2011)
This article describes the scientific definition of innovation. It is investigated and analyzed current problems of the introduction of the innovation process. It is identified key barriers and the principles of innovation, product innovation output constraints on the Ukrainian market.